The impact of strategic control on improving crisis management efficiency in Jordanian industrial companies - Al-Hababi, Salem Muhammad (Journal of Risk and Crisis Management, 2024)
The study focused on demonstrating the impact of strategic control in improving the efficiency of crisis management, and demonstrating the impact of: setting standards, measuring actual performance, evaluating strategic performance, and taking corrective measures in improving crisis management in Jordanian industrial companies. To achieve these goals, the descriptive analytical approach was adopted, and primary data was collected through an electronic questionnaire that was distributed to members of the study sample consisting of general managers and their deputies, department directors, and department heads in public shareholding industrial companies in Jordan. (235) questionnaires were distributed, and (201) questionnaires were retrieved, all of which were valid for statistical analysis. The study used descriptive statistics methods to analyze the data, and also used multiple and stepwise linear regression analysis to test the hypotheses. The study concluded that there is a statistically significant impact of strategic control in improving the efficiency of crisis management in Jordanian industrial companies, and that there is a statistically significant impact of setting standards, measuring actual performance, evaluating strategic performance, and taking corrective measures in improving the efficiency of crisis management in Jordanian industrial companies. The study recommended that corporate management prepare clear crisis management strategies that include identifying potential risks, developing plans to confront them, and using modern technology and data monitoring systems to enhance strategic control and improve response to crises.
Keywords: Strategic Control; Setting Standards; Measuring Actual Performance; Evaluating Strategic Performance; Taking Corrective Measures; Crisis Management; Jordanian Industrial Companies